Decolonizing knowledge: Politics and the aesthetic of 'We' human-and-technology. Issue 3 (1st December 2016) - Cho, Hyunkyoung; Luke, Timothy W.; Yoon, Joonsung
This article suggests that the relations of politics and aesthetics in the flexible, mobile, variable collaborations of computational/informational technologies open a new way of being-and-knowing. By linking art, technology and humanity as the understandings of 'We' human-and-technology in collaborative actions rooted in interdependent perspective, informational technology recomposes both human identity and technological practices as collaborative fusion between the human and technology. The new identity provoked by such technologies might be called 'We' human-and-technology. In this conceptualization of 'We' human-and-technology, the coded complexities of informatics technology remix the axes and dimensions of action between politics and the aesthetic. Prior investigations of the relation of politics and the aesthetic in contemporary art are stuck in the binary frame of domination in which 'Us' versus 'Them' enforces a mutual degradation of the human and technified in thought and action. This approach is criticized here from two perspectives. First, the real disruption of 'We' human-and-technology is a reified inversion by a frame of fantasy, using the tolerance tactic. Second, the traditional instrumental understanding of technology sees it only as an instrument for colonization, which is a limited appraisal of all that happens in technological praxes.